2016
DOI: 10.1134/s1023193516100037
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of bromate anion on inactive RDE under steady-state conditions: Numerical study of ion transport processes and comproportionation reaction

Abstract: International audienceThe study is devoted to analyzing the electroreduction of bromate anion BrO (3) (-) on catalytically inactive (e.g., carbon) electrodes by numerical methods. This process is realized due to the combination of the reversible mediator pair Br-2/Br- and the process of comproportionation (reaction of bromate and bromide anions) in solution phase. These reactions increase the concentration of bromine and bromide near the electrode surface; hence, this process is autocatalytic (ECaEuro(3) mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…In practical terms it is seen from the analysis in section A1.3 of Appendix 1 for weak currents that this approximation reproduces reasonably well all characteristics already for x dk =2, the precision increasing rapidly for larger x dk values. Besides, a similar study for the case of the proton excess compared to bromate [4] demonstrated that the approximation of a thin kinetic layer resulted in predictions for both weak and strong currents which were in conformity with those on the basis of numerical calculations.…”
Section: Appendix 2: Analytical Solution For Small Kinetic Layer Thicsupporting
confidence: 75%
See 4 more Smart Citations
“…In practical terms it is seen from the analysis in section A1.3 of Appendix 1 for weak currents that this approximation reproduces reasonably well all characteristics already for x dk =2, the precision increasing rapidly for larger x dk values. Besides, a similar study for the case of the proton excess compared to bromate [4] demonstrated that the approximation of a thin kinetic layer resulted in predictions for both weak and strong currents which were in conformity with those on the basis of numerical calculations.…”
Section: Appendix 2: Analytical Solution For Small Kinetic Layer Thicsupporting
confidence: 75%
“…outside the kinetic layer. To facilitate the comparison of the results in this study with those in Refs [3,4] we introduce in a similar formal manner the diffusion-limited current of bromate for its transformation to bromine:…”
Section: Dimensionless Variablesmentioning
confidence: 99%
See 3 more Smart Citations